Dıagnostıc Value of IMP3 Expression in Colorectal Carcinoma and Adenoma - Akyol, Hadice; Özercan, İbrahim Hanifi (Yuzuncu Yil Universitesi Tip Fakultesi, 2022)
Colorectal carcinomas are the cause of high mortality and morbidity and are common i n the world and in our country. The main mechanism emphasized in colorectal carcinogenesis is the adenoma-carcinoma sequence. However, carcinoma does not develop from all adenomas. Many factors are effective in the prognosis of colorectal carcinomas. The most important prognostic parameter is TNM staging. Another is lymph node metastasis. In our study, we planned to evaluate the expression of insulin-like growth factor II m-RNA binding protein 3 (IMP3) in colorectal pathologies and its relationship with pro gnostic factors. The 30 colorectal adenocarcinomas (10 well differentiated, 10 moderately differentiated, 10 poorly differentiated), 30 colon adenomas (10 tubular, 10 villous, 10 tubulovillous) and 10 normal colonic mucosa were included in our study. The diagnostic value of the extent and intensity of staining and the relationship between stage and lymph node metastasis in patients stained with IMP3 was investigated. There was a significant correlation between IMP3 and normal mucosa-adenoma and normal mucosa-carcinoma groups (p <0.05), but no significant correlation was found between lymph node metastasis and stage (p> 0.05). Significant correlations were found between IMP3 staining intensity and adenoma-carcinoma groups and between villous adenomas and other adenoma groups (p<0.05). There was no statistical significance between differentiation degrees of carcinomas in IMP3 staining intensity (p>0.05). As a result, it was seen that IMP3 could be used in diagnosis, but the relationship between these markers and lymph node metastasis and stage was not significant. © 2022, Yuzuncu Yil Universitesi Tip Fakultesi. All rights reserved.
Keywords: adenoma; Colorectal carcinoma; IMP3; prognostic factor